Determination of isoniazid in human urine using screen-printed carbon electrode modified with poly-L-histidine - Bergamini, Marcio F.; Santos, Daniela P. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V. Sa, 2010)
A sensitive voltammetric method for trace measurements of isoniazid (INZ) in synthetic human urine sample is described. The method is based on its electroreduction at -0.98 V vs. Ag/AgCl on screen-printed carbon electrode (SPCE) modified with poly-L-histidine (PH). A film of good adherence on SPCE and electrocatalytic properties was obtained coating the electrode by histidine monomer electropolymerization process (SPCE/EPH). The electrochemical behavior of the modified SPCE was investigated by cyclic, linear sweep (LSV), differential pulse (DPV). square-wave voltammetry (SWV), and electrochemical impedance spectroscopy (EIS). Limits of detection of 5.0 x 10(-7) mol L(-1), 1.7 x 10(-7) mol L(-1) and 2.5 x 10(-7) mol L(-1) were estimated from LSV, DPV and SWV determinations, respectively. The method was successfully applied to the determination of INZ in human urine samples. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Screen-printed electrode; Modified electrode; Poly-L-histidine; Isoniazid; Determination